The negligent nuisance / Ismail Brahim - Brahim, Ismail (Faculty of Law, 1986)
In ‘The Wagon Mound’1 the Privy Council had to consider claims in public nuisance and negligence arising out of the original accident in Sydney Harbour. The decision in this case has given a fresh life to discussion of the relationship between Nuisance and Negligence. The judgement leaves obscure the relationship between these torts. The Privy Council do not claim to have assimilated them, but in Goldman v Hargrave2 the court states las this Board has recently explained in the Wagon Mound (No.2) the tort of nuisance, uncertain in its boundary, may comprise a wide variety of situations, in some of which negligence plays no part, in others of which it is decisive. I n the Wagon Mound (No: 2) , ‘foreseeability’ , 'negligence' and fault are jostled together without any clear analysis of the relationship between these concepts or their proper roles in deciding actions in different torts.